RESPON TANAMAN KEDELAI (Glycine max (L) Merril) TERHADAP ETHEPON PADA JARAK TANAM YANG BERBEDA - Tondang, Dewi A; Rasyad, Aslim; ', Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this researchis to determine the response of soybean (Glycine max (L) Merril) on application of ethepon under two planting spaces and to determine the concentration of ethepon application for a specific planting space.A field experiment was conducted by using split plot design, in which four levels of ethepon concentration ie; 100 ppm, 200 ppm, 300 ppm and control were assigned to main plots and two levels of planting spaces ie; 40 cm x 15 cm and   40 cm x 20 cm were assigned as subplot. Parameters observed were plant height 35 days after planting, number of primary branches, internode length of the main stem, plant growth rate, leaf area index, days to flowering, grain yield per plot , and 100-seed weight. The data were analyzed by analysis of variance andfurther investigated by least significant difference atp = 0.05. The result shown thatethepon application tented to shorten plant height and internodes height, lessen the number of primary branches, decreased leaf area and leaf area index, accelerate flowering dates and decreased grain yield per plot, but not for 100-seed weight. The implication drawn from this research was that application of ethepon could not be recommended for soybean.   Keywords: soybean, ethepon, plant spacing